2001
DOI: 10.4049/jimmunol.167.9.4828
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin-1 and IL-2 Synergize to Induce IFN-γ Expression in Human Peripheral Blood T Cells: Implications for Cancer Immunotherapy

Abstract: Bryostatin-1 (Bryo-1), a protein kinase C modulator with antineoplastic activity, may exert some of its antitumor activity through activation of the immune response. Studies in tumor-bearing hosts have indicated that the T cell response, particularly IFN-γ production, is impaired. To evaluate whether Bryo-1 plus IL-2 may affect the activation pattern of T cells, we investigated the expression of IFN-γ mRNA and protein in human primary T cells. Northern blot analysis and ELISAs demonstrated that Bryo-1 and IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…As a consequence, BI has a short-lived effect on ERK-1/2 phosphorylation (1-3 h) that is overcome after 6 -12 h of treatment with bryostatin-1, the time needed for the optimal induction of CD20 mRNA in NHL cells. Bryostatin-1 can induce gene expression also through p38 MAPK signaling pathway (32). Our results indicated that the effects of bryostatin-1 on CD20 mRNA expression or ERK-1/2 phosphorylation were not mediated by p38 MAPK (Figs.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…As a consequence, BI has a short-lived effect on ERK-1/2 phosphorylation (1-3 h) that is overcome after 6 -12 h of treatment with bryostatin-1, the time needed for the optimal induction of CD20 mRNA in NHL cells. Bryostatin-1 can induce gene expression also through p38 MAPK signaling pathway (32). Our results indicated that the effects of bryostatin-1 on CD20 mRNA expression or ERK-1/2 phosphorylation were not mediated by p38 MAPK (Figs.…”
Section: Discussionsupporting
confidence: 50%
“…The effects of bryostatin-1 are mediated through numerous pathways, including PKC, p38 MAPK, ERK-1/2, and others (32,59,65,66). It has been shown that bryostatin-1 activates the MEK/ ERK pathway (65,66).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In almost all cases, this increased stability was shown to be dependent upon p38 mitogen activated protein kinase (p38 MAPK) activity, as the stability was not observed when inhibitors of this pathway were included in the assay. These various stimulations include: treatment of T and NK cells with IL-2 + IL-12 [28][29][30][31][32]; IL-12 + IL-18 treatment of NK cells [32]; anti-CD3 + anti-CD28 or anti-CD2 treatment of T cells [33] with a similar study comparing cells obtained from old and young mice [34]; CD4+ memory T cells activated by OX40L [35]; treatment of both CD4+ and CD8+ T cells with IL-2 and bryostatin [36]; and stimulation of Jurkat T cells with anti-LFA1 and anti-CD3 [37]. In addition, our laboratory (H.A.Y.)…”
Section: Post-transcriptional Control Of Ifn-γ Productionmentioning
confidence: 99%